The Interviewer in the Respondent's Shoes: What Can We Learn from the Way Interviewers Answer Survey Questions?. Issue 2 (May 2017) - Wuyts, Celine; Loosveldt, Geert
Previous research shows that interviewers to some extent fail to expend the effort that is needed to collect high-quality survey data. We extend the idea of interviewer satisficing to a related task, in which the interviewers themselves answer survey questions. We hypothesize that interviewers who self-administer the questionnaire in a careless manner will also not apply themselves fully to the task of administering survey interviews. Based on interviewer and respondent data from the sixth round of the European Social Survey in Belgium, we find support for some of the hypothesized associations between (suboptimal) response characteristics of interviewers in the "task as respondent" and the same (suboptimal) response characteristics recorded for their respondents, specifically with regard to interview speed, multiple response, and item nonresponse to the household income question.